Sialidases From Clostridium perfringens and Their Inhibitors - Wang, Yan-hua (Frontiers in Cellular and Infection Microbiology, 2020)
Clostridium perfringens is an important human and animal pathogen that is the primary causative agent of necrotizing enteritis and enterotoxemia in many types of animals; it causes traumatic gas gangrene in humans and animals and is associated with cases of food poisoning in humans. C. perfringens produces a variety of toxins as well as many enzymes, including three sialidases, NanH, NanI, and NanJ. Sialidases could be important virulence factors that promote the pathogenesis of C. perfringens. Among them, NanI promotes the colonization of C. perfringens in the intestinal tract and enhances the cytotoxic activity and association of several major C. perfringens toxins with host cells. In recent years, studies on the structure and functions of sialidases have yielded interesting results, and the functions of sialic acid and sialidases in bacterial pathogenesis have become a hot research topic. An in-depth understanding and additional studies of sialidases will further elucidate mechanisms of C. perfringens pathogenesis and could promote the development and clinical applications of sialidase inhibitors. This article reviews the structural characteristics, expression regulation, roles of sialidases in C. perfringens pathogenesis, and effects of their inhibitors.